LOVE MADNESS - Zahurska, N. V. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2017)
The article explores the philosophic-anthropological aspects of love madness with an emphasis on its creative potential. Special attention is paid to the topology of love madness, in particular the topos fly’n’burn and fall in/out. The specifics of delusional division of subjectivity and its textual manifestations are studied. Thinking in this case appears as a systematization of attempts not to think. The ratio of love madness to brutality of sexuality as a criterion of becoming in distinction is considered. Processuality in this context appears as a self-conscious affirmation of love madness.